2021
DOI: 10.1016/j.psychres.2021.113802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the first Covid-19 pandemic wave on first episode psychosis in Milan, italy.

Abstract: The ongoing Corona Virus Disease 2019 (COVID–19) pandemic appears to increase risk for mental illness, either directly due to inflammation caused by the virus or indirectly due to related psychosocial stress, resulting in the development of both anxious-depressive and psychotic symptoms. The purpose of the present study was to assess the frequency and characteristics of all patients with First Episodes Psychosis (FEP) without COVID-19 infection hospitalized in the first four months since lockdown in Milan. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 43 publications
(33 reference statements)
4
35
1
1
Order By: Relevance
“…Only the diagnosis groups F10–F19 and F20–F29 show a numerical increase in the percentage of cumulative admissions in 2020 as compared to the previous years. It is interesting to note in this context, that recent reports indicate an increase in the utilization of psychiatric treatment for these diagnosis groups ( Esposito et al, 2021 ; Melamed et al, 2020 ). It needs to be assessed in further studies, whether specific psychiatric disorders will be more affected by the COVID-19 pandemic in the future ( Ambrosetti et al, 2021 ; Tromans et al, 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…Only the diagnosis groups F10–F19 and F20–F29 show a numerical increase in the percentage of cumulative admissions in 2020 as compared to the previous years. It is interesting to note in this context, that recent reports indicate an increase in the utilization of psychiatric treatment for these diagnosis groups ( Esposito et al, 2021 ; Melamed et al, 2020 ). It needs to be assessed in further studies, whether specific psychiatric disorders will be more affected by the COVID-19 pandemic in the future ( Ambrosetti et al, 2021 ; Tromans et al, 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…Studies examining trends of psychiatric referrals and emergency visits found an overall decrease in the number of presentations 15 – 17 . A relative increase in psychotic and manic presentation was observed in some studies, as well as increased severity, manifested in greater numbers of involuntary admissions 15 , 17 , 18 . Other studies, however, report similar or slight decrease in psychotic cases 16 , 19 .While studies acknowledged the different pathways in which the pandemic can affect these trends (biological vs psychological and sociological), results were conflicting, whether COVID19 positive patients were more likely to be psychotic 19 , or no difference was observed between COVID19 positive and negative patients 15 .…”
Section: Introductionmentioning
confidence: 83%
“…These events have been associated to a deterioration of psychological health and have been recognized as potential triggers for various mental-health diseases, including first episodes of psychosis [ 3 ] and post-traumatic stress disorder (PTSD) [ 4 , 5 ]. Psychological impairment has particularly severe consequences on healthcare workers also impacting public health by diminishing psychological resources, working abilities and competences, potentially causing inappropriate, negligent and careless behaviors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%